SOCIAL COMPLEXITY AND LEARNING FORAGING TASKS IN BEES - AMAYA-MÁRQUEZ MARISOL; WELLS HARRINGTON (Caldasia)
Social complexity and models concerning central place foraging were tested with respect to learning predictions using the social honey bee (Apis mellifera ) and solitary blue orchard bee (Osmia lignaria) when given foraging problems. Both species were presented the same foraging problems, where 1) only reward molarity varied between flower morphs, and 2) only reward volume varied between flower morphs. Experiments utilized blue vs. white flower patches to standardize rewards in each experimental situation. Although honey bees learned faster than blue orchard bees when given a molarity difference reward problem, there was no significant difference in learning rate when presented a volume difference reward problem. Further, the rate at which blue orchard bees learned the volume difference problem was not significantly different from that with which honey bees learned about reward molarity differences. The results do not support the predictions of the social complexity theory, but do support those of the central place model